Jazz - Giddins, Gary; De Veaux, Scott K. (New York Norton, 2009)
History of jazz that explains what jazz is, where it came from, and who created it and why, all within the broader context of American life and culture. Emphasizing its African American roots, Jazz traces the history of the music over the last hundred years. From ragtime and blues to the international craze for swing, from the heated protests of the avant-garde to the radical diversity of today's artists, Jazz describes the travails and triumphs of musical innovators struggling for work, respect, and cultural acceptance set against the backdrop of American history, commerce, and politics. With vibrant photographs by legendary jazz chronicler Herman Leonard, Jazz is also an arresting visual history of a century of music.
Musical orientation : elements and instruments -- Jazz form and improvisation -- The roots of jazz -- New Orleans -- New York in the 1920s -- Louis Armstrong and the first great soloists -- Swing bands -- Count Basie and Duke Ellington -- A world of soloists -- Rhythm in transition -- Modern jazz : bebop -- The 1950s : cool jazz and hard bop -- Jazz composition in the 1950s -- Modality : Miles Davis and John Coltrane -- The avant-garde -- Fusion I : R&B, singers, and Latin jazz -- Fusion II : jazz, rock, and beyond -- Historicism : jazz on jazz -- Jazz today -- Selected musicians on primary jazz instruments -- Glossary -- Collecting jazz recordings -- Jazz on film.
Includes bibliographical references (p. 665-675) and index.
Keywords: Jazz -- History and criticism -- United States